Quality of life in patients with stage 5 chronic kidney disease and type 2 diabetes: A cross-sectional study - Mumtaz, Syakira; Dianingati, Ragil Setia; Annisaa', Eva; Riewpaiboon, Arthorn (Universitas Muhammadiyah Magelang, 2024)
Diabetic Chronic Kidney Disease is a complication of diabetes marked by a progressive decline in kidney function. When kidney function falls below a glomerular filtration rate (GFR) of 15 ml/min (Stage 5), patients require renal replacement therapies, such as hemodialysis. This condition can significantly impact a patient's quality of life. This study aims to identify patient characteristics, assess quality of life, and explore the relationship between patient characteristics and quality of life in individuals with Type 2 Diabetes Mellitus complicated by Stage 5 Chronic Kidney Disease at RSUP Dr. Kariadi Semarang. The research used a cross-sectional design and the KDQoL-SF36 questionnaire for data collection. Results indicate that the patient group was predominantly elderly (90.7%), male (62.8%), married (88.37%), and primarily educated at the primary or secondary level (74.42%). A majority were unemployed (53.49%) and had an income greater than 3.000.000 IDR (62.79%). Most patients had been diagnosed with CKD Stage 5 for ≤12 months (62.79%), were receiving monotherapy for diabetes management (58.14%), and had more than one comorbidity (90.7%). The overall quality of life was rated favorably, with an average score of 72.09%. The study concludes that, while the quality of life is generally favorable, it is not significantly influenced by the specific patient characteristics examined. No correlation was found between these characteristics and the quality of life in patients with Type 2 Diabetes Mellitus and Stage 5 Chronic Kidney Disease at RSUP Dr. Kariadi Semarang. Keywords: Cross-sectional study; kidney disease; prevention; quality of life; type 2 diabetes